Smart Government Resilience & Cybersecurity Risk Management - DALI, HOOR RIADH (2020)
In smart government systems, there is a high level of local and global business interconnectedness, which increases the overall vulnerability on the cyber platform. Usually, the highest risk can be found in the smart infrastructure of smart government. Consequently, this needs to be protected and safeguarded. In order to be effectively equipped, the establishment of a sophisticated cyber resilience framework is essential. Smart governments need to be well-prepared (managerially) and well-equipped (technically); especially in times of cybersecurity crisis. For this purpose, the researcher reviewed and evaluated the existing resilience frameworks worldwide and developed a proposed framework for the smart governments in the UAE. This study determined and identified the components of the resilience framework, which addresses the above issues and results in smart government resiliency and cybersecurity risk management. This research contributed to filling the gap in the literature, particularly in Resilient Measurement in relation to cybersecurity, especially in the case of smart government systems. The suggested model matches the smart government needs/culture in the UAE according to this study survey, which measured the readiness and determined maturity level of the smart systems analysed. The researcher adopted a quantitative research methodology for this work. Responses from 432 smart services users in the UAE were collected and analysed. It was discovered that the proposed resilience structure can be adopted successfully by the smart government enterprise. It has assessed the flexibility of the electronic platform procedures to fill the gap in sustainability materials related to smart government resilience structures and cybersecurity risk management; and found the best current resiliency framework.